Making the Geologic Now: Responses to Material Conditions of Contemporary Life - Ellsworth, Elisabeth; Kruse, Jamie (punctum books, 2012)
Making the Geologic Now announces shifts in cultural sensibilities and practices. It offers early sightings of an increasingly widespread turn toward the geologic as source of explanation, motivation, and inspiration for creative responses to conditions of the present moment. In the spirit of a broadside, this edited collection circulates images and short essays from over 40 artists, designers, architects, scholars, and journalists who are actively exploring and creatively responding to the geologic depth of "now." Contributors' ideas and works are drawn from architecture, design, contemporary philosophy and art. They are offered as test sites for what might become thinkable or possible if humans were to collectively take up the geologic as our instructive co-designer-as a partner in designing thoughts, objects, systems, and experiences. Recent natural and human-made events triggered by or triggering the geologic have made volatile earth forces sense-able and relevant with new levels of intensity. As a condition of contemporary life in 2012, the geologic "now" is lived as a cascade of events. Humans and what we build participate in their unfolding. Today, and unlike the environmental movements of the 1970s, the geologic counts as "the environment" and invites us to extend our active awareness of inhabitation out to the cosmos and down to the Earth's iron core.